PENGARUH VARIASI PRODUK DAN KUALITAS PELAYANAN KONSUMEN TERHADAP MINAT BELI ULANG KONSUMEN PADA WARUNG MAKAN NOSTIMO BALIKPAPAN - Prihandoyo, Prihandoyo; Hernadi Moorcy, Nadi; Tangke Rante, Nely (Jurnal GeoEkonomi, 2025)
This study aims to examine the effect of product variety and service quality on consumer repurchase intention at Nostimo Food Stall, Balikpapan. This study uses a quantitative approach and uses primary data obtained from 246 respondents as samples selected based on convenience sampling method. The collected data were analyzed based on multiple linear regression analysis using SPSS. The result shows that product variation and service quality have a significant effect simultaneously on consumer repurchase intention. The product variety has a positive and significant effect on consumer repurchase interest, but service quality has a positive and insignificant effect on consumer repurchase interest. The results provide managerial implications for Nestimo Balikpapan Food Stalls to increase its product variety and improve health protocol-based services in order to increase consumer repurchase interest. With the increase of consumers' repurchase interest, it is expected that this restaurant business that is run can develop and be sustainable. Confirming that the combination of both creates a satisfying eating experience and increases consumer loyalty. These findings provide important insights for culinary entrepreneurs in improving their competitiveness. Despite this success, the researcher still recommends exploring the impact of additional factors such as digital customer experience and social media-based marketing strategies on repurchase intention. In addition, a more in-depth study of market segmentation based on demographics could provide additional insights into different consumer preferences.